2012
DOI: 10.7324/japs.2012.2405
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive activity of the methanol extracts of leaves of Eugenia fruticosa (Roxb.) and Glycosmis pentaphylla (Retz.) in Swiss albino mice

Abstract: The present study was designed to evaluate analgesic potential of the methanolic extracts of the leaves of the both Glycosmis pentaphylla (Rutaceae) and Eugenia fruticosa (Myrtaceae). The analgesic activity was evaluated using the acetic acid (0.7% i.p.)-induced writhing inhibition method in swiss albino mice. The methanolic extract of leaves of Glycosmis pentaphylla, at the dose of 200 and 400 mg/kg body weight significantly (p<0.001) reduced the number of writhes with 31.97% and 44.21% of inhibition, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The methanol extract of G. pentaphylla administered at doses of 200 and 400 mg/kg body weight inhibited the acetic acid-induced writhing in mice by 31.97 and 44.21%, respectively, compared to the standard diclofenac (50 mg/kg dose) which reduced writhes by 65.31% (Shams- Ud-Doha et al, 2012). Another similarly designed study reported 36.54 and 57.70% reductions in writhing counts for the methanol extract at doses of 250 and 500 mg/kg body weight, indicating prominent dose-dependent analgesic property for the extract (Sarkar et al, 2013).…”
Section: Analgesic Activitymentioning
confidence: 99%
“…The methanol extract of G. pentaphylla administered at doses of 200 and 400 mg/kg body weight inhibited the acetic acid-induced writhing in mice by 31.97 and 44.21%, respectively, compared to the standard diclofenac (50 mg/kg dose) which reduced writhes by 65.31% (Shams- Ud-Doha et al, 2012). Another similarly designed study reported 36.54 and 57.70% reductions in writhing counts for the methanol extract at doses of 250 and 500 mg/kg body weight, indicating prominent dose-dependent analgesic property for the extract (Sarkar et al, 2013).…”
Section: Analgesic Activitymentioning
confidence: 99%
“…G. pentaphylla is a perennial shrub indigenous to the tropical and subtropical regions of China, India, Sri Lanka, Bangladesh, Indonesia, Myanmar, Malaysia, Thailand, the Philippines, Java, Vietnam, Sumatra, Borneo, and Australia. , These plants are traditionally used to treat a variety of ailments including rheumatism, urinary tract infections, chest pain, anemia, cough, liver disorders, inflammation, pain, fever, jaundice, bronchitis, bone fractures, toothache, gonorrhea, diabetes, cancer, and other chronic diseases. , An extensive literature search on phytochemistry of G. pentaphylla revealed that various parts of this plant were reported to contain at least 354 secondary metabolites such as acridone, carbazole, quinolone, and quinazoline types of alkaloids, flavonoids, phenolic glycosides, quinones, furoquinolines, terpenoids, steroids, sulfur-containing amides, gums, reducing sugars, tannins, saponins, and fatty derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Glycosmis pentaphylla ( G. pentaphylla ) is a flowering small plant or evergreen shrub belongs to Rutaceae family. It is mainly found in East as well as Southeast Asia [24] . Numerous active constituents were identified in G. pentaphylla such as arborine, flavonoids, terpenoids, alkaloids, coumarins, amides and imides [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%